Academia's Golden Age 1992
DOI: 10.1093/oso/9780195054644.003.0008
|View full text |Cite
|
Sign up to set email alerts
|

The World Transformed: A Golden Age for American Universities, 1945–1970

Abstract: In the years following World War II, academic leaders in Massachusetts participated in a national debate about the social role of higher education in the era that lay ahead. They also experienced the beginnings of a period of expansion for universities that would continue, more or less uninterrupted, for twenty-five years. Change in this postwar golden age involved an ongoing interaction between ideas and opportunities: the first concerning the public purposes of higher education; the second promising glory fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Bill, and the federal Pell Grant system. Freeland (2007) reported that the number of servicemen who utilized the G.I. Bill within 5 years of the war’s end exceeded the highest estimates by 300%.…”
Section: Evidence For Access and Successmentioning
confidence: 99%
“…Bill, and the federal Pell Grant system. Freeland (2007) reported that the number of servicemen who utilized the G.I. Bill within 5 years of the war’s end exceeded the highest estimates by 300%.…”
Section: Evidence For Access and Successmentioning
confidence: 99%
“…According to this belief, institutions of higher learning have generally provided an educational product that varies little from college to college (Trow, 1988), with the education service provided being fairly standardized (Goodchild, 1986). Institutions did not respond to the specific needs of students due to consistently high demand for admission (Freeland, 1992). This situation has changed markedly in the United States since the 1940s (Kerr, 1984).…”
Section: Historical Perspectivementioning
confidence: 99%
“…In the mid-20 th century, higher education began to shift towards mass access. There was a massive expansion of college enrollment partially due to the GI bill, which increased veteran access to higher education (Arendale, 2010;Cohen & Kisker, 2010;Freeland, 1997;Thelin, 2011). According to Arendale (2010) and Cohen and Kisker (2010), the dramatic enrollment increase in higher education led to an increase in learning assistance and remedial coursework to prepare students academically.…”
Section: Higher Education and Learning Assistancementioning
confidence: 99%
“…The landscape of higher education and learning assistance programs changed dramatically during the period from 1945 to 1970. After World War II, the GI bill provided returning veterans with funds to pursue postsecondary learning, which resulted in booming enrollments (Cohen & Kisker, 2010;Freeland, 1997;Thelin, 2011). This unprecedented public investment in higher education and corresponding high demand for postsecondary offerings necessitated increased utilization of standardized testing for admissions, and because many new enrollees were academically unprepared, there were also high attrition rates in the first and second years (Cohen & Kisker, 2010;Thelin, 2011).…”
Section: Higher Education and Learning Assistancementioning
confidence: 99%